(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Clinical manifestations of coloboma and a pit of the optic disc are variable, which conditions the need for differentiated diagnosis of this rare pathology and proper treatment. The article describes characteristics of diagnosis and clinical course of optic nerve coloboma in dynamics.